2009
DOI: 10.1111/j.1464-410x.2009.08369.x
|View full text |Cite
|
Sign up to set email alerts
|

The overlap of storage, voiding and postmicturition symptoms and implications for treatment seeking in the USA, UK and Sweden: EpiLUTS

Abstract: seeking as the dependent variable and the bother of individual symptoms as predictors. RESULTSThe survey response rate was 59%. The sample included 30 000 participants (14 139 men and 15 861 women); 71% of men and 75% of women reported at least one LUTS, and about half reported LUTS from more than one symptom group. Rates of bother were greatest for those who reported multiple storage, voiding and postmicturition LUTS (men 83%, women 89%). Less than a third of participants with LUTS from all three groups repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
156
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 176 publications
(171 citation statements)
references
References 47 publications
11
156
0
4
Order By: Relevance
“…Similar results have been described in the EpiLUTS survey, which reported that only 11.2-17.6% of men with LUTS and both storage and voiding symptoms were prescribed medication 18 . Initial treatment with a 1 -blocker monotherapy may not adequately control symptoms in men with storage symptoms based on data which reported only 35% of men had improved symptoms with a 1 -blocker monotherapy, whilst a 1 -blocker plus antimuscarinic combination therapy improved symptoms in 73% of those men who did not initially respond to a 1 -blocker monotherapy 19 .…”
Section: Discussionsupporting
confidence: 86%
“…Similar results have been described in the EpiLUTS survey, which reported that only 11.2-17.6% of men with LUTS and both storage and voiding symptoms were prescribed medication 18 . Initial treatment with a 1 -blocker monotherapy may not adequately control symptoms in men with storage symptoms based on data which reported only 35% of men had improved symptoms with a 1 -blocker monotherapy, whilst a 1 -blocker plus antimuscarinic combination therapy improved symptoms in 73% of those men who did not initially respond to a 1 -blocker monotherapy 19 .…”
Section: Discussionsupporting
confidence: 86%
“…Lower urinary tract symptoms (LUTS) in men are categorized into storage symptoms (increased daytime urinary frequency, nocturia, urgency, and incontinence), voiding symptoms (slow stream, splitting or spraying, intermittent stream, hesitancy, straining, and terminal dribble), and post-micturition symptoms (feeling of incomplete emptying and post-micturition dribble) (Abrams et al, 2002;Sexton et al, 2009). The International Prostate Symptom Score (IPSS) questionnaire investigates the presence of these symptoms in seven questions, allowing to establish the severity/quantification of LUTS (Barry, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This finding revealed that LUTS severity is associated anxiety and QoL consisted with previous study. LUTS which contains obstructive (voiding) symptoms and irritative (storage) symptoms can be quantitatively assessed by questionnaires like the IPSS [2][3][4]. In Tanik's study, Qmax and IPSS were correlated with prostate volume, which is related with the clinical status of patients [15].…”
Section: Discussionmentioning
confidence: 99%
“…Lower urinary tract symptoms (LUTS) secondary to BPH are prevalent and interfere with the quality of life (QoL) of older men [2][3][4]. The prevalence of BPH is about 40% for men in their fifties and reaches to 90% for men in their nineties [5].…”
Section: Introductionmentioning
confidence: 99%